Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pone.0227965
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and foetomaternal effects of iron deficiency anaemia among pregnant women in Lagos, Nigeria

Abstract: Anaemia in pregnancy is a major health problem and an important cause of adverse foetomaternal outcomes in developing countries. Iron deficiency is the cause of the overwhelming majority of the cases of anaemia in pregnancy. Iron deficiency anaemia (IDA) has been linked with adverse foetal and maternal outcomes. This study investigated the prevalence of IDA and evaluated its effects on foetomaternal outcomes among parturients in Lagos, Nigeria. This was a cross-sectional study that enrolled 220 women aged 15-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 24 publications
3
21
2
Order By: Relevance
“…In addition, positive association for preterm birth and anemia was evidenced in non-white women, living in the Northeast region, schooling years less than 8, presence of children below 5 years old, onset of prenatal care at second or third trimester and less than six prenatal care visits. These findings are consistent with literature as anemia is associated with poor access to antenatal care and low socio-economic condition [5,17,18]. In our country, non-white skin color and the Northeast region are associated with lower income regions and therefore associated with anemia [25].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, positive association for preterm birth and anemia was evidenced in non-white women, living in the Northeast region, schooling years less than 8, presence of children below 5 years old, onset of prenatal care at second or third trimester and less than six prenatal care visits. These findings are consistent with literature as anemia is associated with poor access to antenatal care and low socio-economic condition [5,17,18]. In our country, non-white skin color and the Northeast region are associated with lower income regions and therefore associated with anemia [25].…”
Section: Discussionsupporting
confidence: 92%
“…Our results also found association with maternal age and the presence of anemia in preterm deliveries, as it was more frequent in pregnant adolescents. This is in agreement with the Chinese study that found higher prevalence of anemia in women under 20 [17]. In addition, positive association for preterm birth and anemia was evidenced in non-white women, living in the Northeast region, schooling years less than 8, presence of children below 5 years old, onset of prenatal care at second or third trimester and less than six prenatal care visits.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Anaemia prevalence is common around the globe but most prevalent in developing countries. Prevalence of anaemia was recorded higher in the South Asian and African continent than in other countries throughout the world (Ajepe et al, 2020).Global estimation indicated that three out of ten (29%) of non-pregnant women and more than one third (38%) were anaemic (Herzog et al, 2019;Kay et al, 2019). It is estimated that nearly half a billion of women from reproductive age are affected by anaemia (Wemakor, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…During the survey, we were somewhat astonished to note that multiple pregnant women never prefer to consume animal entrails before pregnancy, which may be one of the reasons why the participants had such a severe iron-rich food deficiency during pregnancy. Since iron-rich food deficiency is related to premature, postpartum hemorrhage, and low birth weight, it is indispensable to augment the intake of ironrich foods during pregnancy [29,30]. Besides, soybean and its products, aquatic products, milk and milk products, eggs, and meats are generally considered favorable sources of high-quality protein and minerals, yet more than 60% of participants did not meet the recommended intake.…”
Section: Discussionmentioning
confidence: 99%